Illustrated State‐of‐the‐Art Capsules of the ISTH 2022 Congress. Issue 5 (6th July 2022) - Ariëns, Robert A.; Hunt, Beverley J.; Agbani, Ejaife O.; Ahnström, Josefin; Ahrends, Robert; Alikhan, Raza; Assinger, Alice; Bagoly, Zsuzsa; Balduini, Alessandra; Barbon, Elena; Barrett, Christopher D.; Batty, Paul; et al.
Abstract: The ISTH London 2022 Congress is the first held (mostly) face‐to‐face again since the COVID‐19 pandemic took the world by surprise in 2020. For 2 years we met virtually, but this year's in‐person format will allow the ever‐so‐important and quintessential creativity and networking to flow again. What a pleasure and joy to be able to see everyone! Importantly, all conference proceedings are also streamed (and available recorded) online for those unable to travel on this occasion. This ensures no one misses out. The 2022 scientific program highlights new developments in hemophilia and its treatment, acquired and other inherited bleeding disorders, thromboinflammation, platelets and coagulation, clot structure and composition, fibrinolysis, vascular biology, venous thromboembolism, women's health, arterial thrombosis, pediatrics, COVID‐related thrombosis, vaccine‐induced thrombocytopenia with thrombosis, and omics and diagnostics. These areas are elegantly reviewed in this Illustrated Review article. The Illustrated Review is a highlight of the ISTH Congress. The format lends itself very well to explaining the science, and the collection of beautiful graphical summaries of recent developments in the field are stunning and self‐explanatory. This clever and effective way to communicate research is revolutionary and different from traditional formats. We hope you enjoy this article and will be inspired by its content to generate new research ideas. Abstract :